Efficacy of Honey on Sex Reversal of Guppy (Poecilia reticulata Peters) - D.T. Soelistyowati; E. Martati; H. Arfah (Jurnal Akuakultur Indonesia)
This study was performed to determine effectiveness of honey on sex reversal of guppy.  Guppy broodstock was dipped on 1 L of water containing 0, 20, 40 or 60 mL of honey, for 10 hours.  Sex identification was carried out by morphologically and histological method.  The results of study show that percentage of male progeny tends to increase by increasing the dose of honey used.  Higher percentage of male fish is obtained by the dose of 60 ml/L (59.5% male), about 2.4 fold higher than that of control (24.3% male).  Dipping of honey has no effect on survival of broodstock and larvae.